Il campo dell’essere. Alcune note su poesia e psicoanalisi (ENTHYMEMA, 2019)
The following paper addresses the huge complexity of the relationship psychoanalysis / poetry. It explores the theoretical hypothesis according to which the poetic element can be characterized as the search for a ‘state of being’ constituted through processes of ‘negativization’ of the object. Such processes would give form to the attempt of rediscovering original conditions which inspire different ways of moving across language. To say no to the world, then: in order to realize, as Alain Badiou writes, “the incessant migration towards heteroclite phenomena”. Thus, expressing the affirmative significance of poetry.
Keywords: poetic moment; psychoanalysis; negativization procedures; singularity